2018
DOI: 10.1371/journal.pgen.1007339
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular assembly of the beta-catenin destruction complex and the effect of Wnt signaling on its localization, molecular size, and activity in vivo

Abstract: Wnt signaling provides a paradigm for cell-cell signals that regulate embryonic development and stem cell homeostasis and are inappropriately activated in cancers. The tumor suppressors APC and Axin form the core of the multiprotein destruction complex, which targets the Wnt-effector beta-catenin for phosphorylation, ubiquitination and destruction. Based on earlier work, we hypothesize that the destruction complex is a supramolecular entity that self-assembles by Axin and APC polymerization, and that regulatin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
108
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(120 citation statements)
references
References 75 publications
12
108
0
Order By: Relevance
“…In our recent work, we explored the role of Dsh. We found that overall protein levels of Axin, APC2 and Dsh in Drosophila embryos experiencing active Wnt signaling are within a few-fold of one another, suggesting that competition is a plausible mechanism for destruction complex down-regulation (Schaefer et al, 2018). The competition model is also consistent with the effects of elevating Axin levels, which makes the destruction complex more resistant to turn-down (Cliffe et al,…”
supporting
confidence: 52%
See 4 more Smart Citations
“…In our recent work, we explored the role of Dsh. We found that overall protein levels of Axin, APC2 and Dsh in Drosophila embryos experiencing active Wnt signaling are within a few-fold of one another, suggesting that competition is a plausible mechanism for destruction complex down-regulation (Schaefer et al, 2018). The competition model is also consistent with the effects of elevating Axin levels, which makes the destruction complex more resistant to turn-down (Cliffe et al,…”
supporting
confidence: 52%
“…Wnt signaling triggers down-regulation of the destruction complex, and the ability to do so depends on relative Axin levels. Thus, while a 3-4 fold increase in Axin levels is tolerated by the developing embryo (Wang et al, 2016;Schaefer et al, 2018), more substantial increases in Axin levels prevent inactivation of the destruction complex even in cells exposed to the Wnt ligand (Willert et al, 1999;Cliffe et al, 2003;Schaefer et al, 2018). Dsh is a key positive effector of Wnt signaling and its ability to homopolymerize and to heteropolymerize with Axin are critical for downregulating the destruction complex (Schwarz-Romond et al, 2007a;Schwarz-Romond et al, 2007b;Fiedler et al, 2011;Mendoza-Topaz et al, 2011).…”
Section: Exploring How Dsh Axin and Apc Cooperate And Compete To Modmentioning
confidence: 99%
See 3 more Smart Citations